Cardiac troponin elevation predicts all-cause mortality in patients with acute exacerbation of chronic obstructive pulmonary disease: Systematic review and meta-analysis. (15th July 2015) - Pavasini, Rita; d'Ascenzo, Fabrizio; Campo, Gianluca; Biscaglia, Simone; Ferri, Alessandra; Contoli, Marco; Papi, Alberto; Ceconi, Claudio; Ferrari, Roberto
Abstract: Background: Cardiovascular disease, especially ischemic heart disease, is a major comorbidity in chronic obstructive pulmonary disease (COPD) patients. Several studies suggested that after acute exacerbation of COPD (AECOPD), there is a significant increase of mortality (cardiac and all-cause) and of myocardial infarction. Whether cardiac troponin (Tn) elevation during AECOPD could be considered a prognostic marker of all-cause mortality is still debated. Methods: To assess the prognostic role of cardiac Tn elevation during AECOPD, we performed a systematic review and meta-analysis. We included studies with patients admitted to the hospital for AECOPD, with at least one Tn assessment and reporting the relationship (after multivariable analysis) between Tn elevation and all-cause mortality. Secondarily, studies were stratified according to: i) type of troponin (Tn I or Tn T), and ii) follow-up length (≤ 6 months vs. > 6 months). Results: Ten studies were included in the systematic review and 8 in the meta-analysis. Cardiac Tn elevation ranges from 18% to 73%. We found that cardiac Tn elevation was significantly related to an increased risk for all-cause mortality (OR 1.69; 95% CI 1.25–2.29; I 2 40%). This finding was independent to the follow-up length of studies (≤ 6 months: OR 3.22; 95% CI 1.31–7.91; > 6 months: OR 1.38; 95% CI 1.02–1.86). Finally, Tn T seems to be more helpful in predicting all-cause mortality as compared to Tn I (OR 1.54; 95% CI 1.2–1.96 vs. OR 3.39, 95% CI 0.86–13.36, respectively). Conclusions: In patients admitted to the hospital for AECOPD, cardiac Tn elevation emerged as an independent predictor of increased risk of all-cause mortality.